Medication safety in intravenous therapy: A compatibility study and analysis of reaction products of dihydralazine and metamizole - Koller, Anna Katharina; Fischer, Oliver; Krebs, Sabine; Heinrich, Markus; Dörje, Frank (Scientia Pharmaceutica, 2020)
The pharmacotherapy of critically ill patients is challenging due to the variety of drugs that have to be applied. As the majority of pharmaceuticals must be administered intravenously because of the critical condition of the patients, the compatibility of co-applied intravenous drugs is crucial for a safe and successful infusion therapy. Antihypertensive therapy was reported by health care professionals to be ineffective in association with concomitant application of dihydralazine and metamizole (dipyrone). As both drugs are administered in German intensive care units, we analyzed their compatibility, examined the mechanisms of underlying dihydralazine degradation, and identified reaction products of dihydralazine and metamizole. Binary combinations were prepared at the high and the low end of the nominal administration concentration. Validated high performance liquid chromatography/ultraviolet absorption (HPLC-UV) analysis was conducted to quantify drug amount and high performance liquid chromatography/mass spectrometry (HPLC-MS) was used to analyze degradation products. The combinations of dihydralazine and metamizole proved to be incompatible as dihydralazine concentration decreased immediately and considerably. Metamizole also slightly decreased over time. Specific degradation products of dihydralazine were identified and a degradation pathway was postulated. Our findings demonstrate that the intravenous co-administration of dihydralazine and metamizole should be strictly avoided due to the incompatibility of these two drugs.
CRIS-Team Scopus Importer:2020-06-02
Keywords: Dihydralazine; HPLC-MS; HPLC-UV; Infusion therapy; Medication safety; Metamizole; Y-site compatibility